2022
DOI: 10.1186/s12958-022-01037-7
|View full text |Cite
|
Sign up to set email alerts
|

hsa-miR-320a-3p and hsa-miR-483-5p levels in human granulosa cells: promising bio-markers of live birth after IVF/ICSI

Abstract: Background MicroRNAs (miRNAs) are considered potential biomarkers for various diseases. This study investigated whether hsa-miR-320a-3p and hsa-miR-483-5p levels in human ovarian granulosa cells derived from follicular fluids are associated with embryo developmental competence. Methods We collected 195 granulosa cells samples and analyzed the treatment outcomes in patients undergoing in vitro fertilization (n = 147) or intracytoplasmic sperm inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In this study, we identified several miRNAs related to pregnancy outcomes, and particularly, the combination of three miRNAs (miR-16-2-3p, miR-378a-3p, and miR-483-5p) had the potential for more precise prediction of pregnancy outcomes. Previous studies have reported downregulation of miR-483-5p in conditioned medium from the pregnant group 38 and in granulosa cells from groups with good-quality embryos and live births 39 , which suggested that miR-483-5p plays an important role in embryo development. miR-378a-3p has been identified as a hatching-associated miRNA in a previous report 40 , although our results are contradictory.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we identified several miRNAs related to pregnancy outcomes, and particularly, the combination of three miRNAs (miR-16-2-3p, miR-378a-3p, and miR-483-5p) had the potential for more precise prediction of pregnancy outcomes. Previous studies have reported downregulation of miR-483-5p in conditioned medium from the pregnant group 38 and in granulosa cells from groups with good-quality embryos and live births 39 , which suggested that miR-483-5p plays an important role in embryo development. miR-378a-3p has been identified as a hatching-associated miRNA in a previous report 40 , although our results are contradictory.…”
Section: Discussionmentioning
confidence: 92%